2018
DOI: 10.3748/wjg.v24.i27.2949
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the prognosis and therapy of colorectal cancer: From bench to bedside

Abstract: MicroRNAs (miRNAs) are small, single-stranded, noncoding RNAs that can post-transcriptionally regulate the expression of various oncogenes and tumor suppressor genes. Dysregulated expression of many miRNAs have been shown to mediate the signaling pathways critical in the multistep carcinogenesis of colorectal cancer (CRC). MiRNAs are stable and protected from RNase-mediated degradation, thereby enabling its detection in biological fluids and archival tissues for biomarker studies. This review focuses on the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 269 publications
(190 reference statements)
0
139
0
Order By: Relevance
“…Consequently, miRNAs are implicated in the regulation of a series of biological behaviors, including cell proliferation, differentiation, metabolism and carcinogenesis (12). Emerging data have revealed that miRNAs are abnormally expressed in almost every type of human cancer, including NSCLC (13), cervical cancer (14), colorectal cancer (15), prostate cancer (16) and breast cancer (17). miRNAs are closely associated with NSCLC occurrence and development through regulation of multiple malignant behaviors, as either oncogenes or tumor suppressors (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, miRNAs are implicated in the regulation of a series of biological behaviors, including cell proliferation, differentiation, metabolism and carcinogenesis (12). Emerging data have revealed that miRNAs are abnormally expressed in almost every type of human cancer, including NSCLC (13), cervical cancer (14), colorectal cancer (15), prostate cancer (16) and breast cancer (17). miRNAs are closely associated with NSCLC occurrence and development through regulation of multiple malignant behaviors, as either oncogenes or tumor suppressors (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when they utilized an antibiotic-treated rat model, all four miRNAs showed lower levels of expression after 6 weeks of antibiotic treatment, but at 2 weeks, half were upregulated and half were downregulated, suggesting a temporal nature to the antibiotic effect on miRNA expression. The potential functional consequences of these changes were not examined and are difficult to predict as let-7b functions as an anti-oncomiRNA (miRNAs that inhibit proto-oncogenes) and miR-141 and miR-200a function as oncomiRNAs in CRC [109][110][111].…”
Section: The Gut Microbiome and Non-coding Rnasmentioning
confidence: 99%
“…miRNAs have been reported to play crucial roles in tumor biological processes, including proliferation, apoptosis, migration, invasion, and differentiation (9). The association of non-coding RNAs especially miRNA dysregulation with the occurrence and development of cancer has been supported by evidence (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%